Hiring and Firing: A Tale of Two Thresholds - Booth, Alison L.; Chen, Yu‐Fu; Zoega, Gylfi (Journal of Labor Economics, 2002)
The negative effect of quits on the willingness of firms to provide on‐the‐job training is well documented in the theoretical literature. Here we explore the strength of this effect by solving a firm’s dynamic optimization problem where there is uncertainty about future productivity and nonzero firing costs. We find that the degree to which quit rates affect hiring depends on the ratio of firing to hiring costs. As this ratio rises, the negative effect of quits becomes less important, eventually reversing itself. We also describe how quit rates affect the firing decision. We highlight some testable implications of our analysis.